Pemurnian Minyak Goreng Bekas Dengan Adsorben Ampas Tebu Untuk Pembuatan Biodisel - Nur Asma Deli; Nina Veronika (Fakultas Teknik Universitas Cenderawasih, 2023)
Biodiesel, which is generally defined as monoalkyl esters from plant and animal fats, is an alternative fuel that has the potential to be used as a substitute for diesel fuel because of its characteristics. Used cooking oil or used cooking oil haD the potential to be processed into biodiesel and this study aims was to produce waste cooking oil into biodiesel from the results of the pre-treatment process of used cooking oil with bagasse waste, to find out the optimum result of the oil pretreatment proces and the raw material used was used cooking oil from the Rocket Chicken Food Court restaurant. Waste from sugarcane bagasse was useful as an adsorption process for the purification of used cooking oil which was able to reduce free fatty acid levels, water content, and impurities levels for the biodiesel process. The optimum particle size of bagasse waste for used cooking oil pretreatment was 30 mesh, with the analytical data was 1.93% of free fatty acid, 0,0018 % for water content and 0,03% of firt level. The results of the Biodiesel analysis from the pre-treatment process were the viscosity was 5.7 Cst, the density was 860 kg/m3 and the acid number was 0.8 mg KOH/g oil. This result was accordance to the indonesian national standard No. 04-7182-2006.